Typhoon Kestana: Asia's Katrina - Kuntjoro, Irene A. (2016)
The devastation and catastrophe wrought by Typhoon Kestana on the Philippines’ capital Manila reflect a huge gap between rising vulnerabilities and preparedness at the national and regional levels. As more climate change results in more devastating cyclones, how can the region better prepare for future emergencies?